Clinical evidence of acupuncture and related therapy in patients with cancer-pain: A protocol for systematic review and meta-analysis. Issue 45 (6th November 2020) - Zeng, Jingchun; Zhou, Runjin; Luo, Zhenke; Zhang, Na; Liu, Zijun; Lin, Guohua
Abstract: Background: Cancer pain (CP) is one of the common complications of cancer. During the treatment, oral medication, radiotherapy and chemotherapy bring certain adverse reactions to patients with CP; a safe way to treat this disease is necessary. Acupuncture and related therapies for CP with few side effects have been gradually accepted. But at present the evidence is insufficient, the related research is not thorough enough. The purpose of this study was to investigate the efficacy and safety of acupuncture and related therapies for CP. Methods: The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines were used to design this protocol. The final study will also be conducted under the PRISMA guidelines for systematic reviews and meta-analysis. An electronic search will be conducted in Medline, Embase, and the Cochrane Central Register of Controlled Trials databases through January 2020. The search will be conducted in English. Risk of bias will be assessed by the Cochrane Collaboration tool and the collected evidence will be nar-ratively synthesized. We will also perform a meta-analysis to pool estimates from studies considered to be homogenous. Subgroup analyses will be based on intervention or overall bias. The strength of evidence will be evaluated by the Grading of Recommendations, Assessment, Development and Evaluation scale. Results: This systematic review will summarize high quality clinical evidence to assess and appraise the effectiveness and safety of acupuncture and related therapies for CP patients. Conclusion: The meta-analysis will assess evidence from randomized controlled trials of acupuncture and related therapies and CP types. INPLASY registration number: INPLASY202040129.